Le city branding à l'épreuve de l'alternance politique à travers l’exemple stéphanois. - Giovanni Sechi (Confins)
The shift from the Fordist city to the entrepreneurial city is coupled by a rise in city branding that integrate urban development strategies. The old industrial cities are the firsts to implement this type of actions. At first, we explore here the reasons that led local actors of Saint-Etienne, a former industrial city, to be pioneers in urban branding. Then we will focus on the relationship between local political alternation and urban branding. In doing so, we propose an analysis of voluntary counter-actions, of urban marketing and of labelling processes that were carried out in this city during the last 40 years. The main question concerns the influence of political alternation in the definition and redefinition of these actions. Our hypothesis is that urban marketing has no "political colour". Rather, mayors tend to personalize their mandate through the promotion of different images, programs and actions compared to their predecessors.